Odpowiedź :
a)
Założenie:
[tex]x>0[/tex]
[tex]log_3x=2[/tex]
[tex]3^2=x[/tex]
[tex]x=9[/tex]
b)
Założenie:
[tex]x>0[/tex]
[tex]log_5x=3[/tex]
[tex]5^3=x[/tex]
[tex]x=125[/tex]
c)
Założenie:
[tex]x>-2[/tex]
[tex]log_2(x+2)=3[/tex]
[tex]2^3=x+2[/tex]
[tex]x+2=8[/tex]
[tex]x=8-2[/tex]
[tex]x=6[/tex]
d)
[tex]log_2(x^2+3x-8)=1[/tex]
[tex]2^1=x^2+3x-8[/tex]
[tex]x^2+3x-8=2[/tex]
[tex]x^2+3x-8-2=0[/tex]
[tex]x^2+3x-10=0[/tex]
[tex]x^2-2x+5x-10=0[/tex]
[tex]x(x-2)+5(x-2)=0[/tex]
[tex](x-2)(x+5)=0[/tex]
[tex]x-2=0 \ \ \ lub\ \ \ x+5=0[/tex]
[tex]x=2\ \ \ \ \ \ \ \ \ \ \ x=-5[/tex]
Sprawdzamy, czy rozwiązanie spełnia równanie
[tex]L=log_2(2^2+3\cdot2-8)=log_2(4+6-8)=log_22=1=P[/tex]
[tex]L=log_2((-5)^2+3\cdot(-5)-8)=log_2(25-15-8)=log_22=1=P[/tex]